The ways of the competitiveness increase of the hospitality industry enterprises - Keranchuk, Tatiana (My University, 2013)
У роботі розглянуті сучасні тенденції розвитку підприємств індустрії гостинності та основні напрямки підвищення рівня конкурентоспроможності вітчизняних підприємств готельного і ресторанного бізнесу. The paper discusses the current trends of hospitality industry and the main directions of improving the competitiveness of domestic enterprises of hotel and restaurant business.
Keywords: конкурентоспроможність; індустрія гостинності; інвестиції; системи резервування; контроллінг; конкурентоспособность; индустрия гостеприимства; инвестиции; сompetitiveness; hospitality industry; investments; reservation systems; controlling; кафедра економіки і права